Unicystic ameloblastoma with rare acanthomatous changes in mural Island - Priyadharsini Nataraj; Rajkumar Krishnan; Krishnakumar Raja; Rameshkumar Annasamy; Ashwini Ravi; Dineshkumar Thayalan (Oral Oncology Reports)
Ameloblastomas are true benign odontogenic epithelial tumours, most frequently found in the jaw. It is the second most typical odontogenic neoplasm after odontoma. The most major odontogenic neoplasm, ameloblastomas come in a variety of clinical, radiological, and histological forms. Unicystic ameloblastomas (UAs) are cystic lesions that have the clinical, radiological, or physical characteristics of jaw cysts, but when examined histologically, display a typical ameloblastomatous epithelium lining the cyst cavities, with or without luminal and/or mural tumour development. UAs are a less common and supposedly less aggressive type of ameloblastomas. A 27 year old male patient reported to the college with the chief complaint of pain in lower right back tooth region since two weeks. Acanthomatous changes in an unicystic ameloblastoma is a very rare presentation. Our case had a rare presentation with Mural type of unicystic ameloblastoma exhibiting acanthomatous changes.